Membangun Jembatan Menuju Kesuksesan: Strategi Efektif dalam Bimbingan dan Konseling Karir - Lianti, Afdha; Daharnis, Daharnis; Ifdil, Ifdil (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
This research aims to conduct a literature review related to effective strategies in career guidance and counseling. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection was carried out by documenting and reviewing all articles related to effective strategies in career guidance and counseling in the period 2020-2024. The articles used in this study were 12 accredited national journal articles obtained from the Google Scholar database using the Publish or Perish application. Based on this research, it is found that there are various strategies applied in career guidance and counseling services. These strategies include the application of theories such as Holland and Trait-and-Factor, modeling technique-based approaches, self-management, group counseling, and the use of interactive digital media. Each strategy contributes significantly to students' career development, both in terms of decision-making maturity, career motivation, and life skills that are relevant to the needs of the world of work.